Germination of phoenix roebelenii seeds - De Castro, A. [UNESP] (2013)
The Phoenix roebelenii O'Brien is one of the most used plants in the Brazilian landscape. The work aimed to study the effect of different fruit harvesting locations, associated with seven temperature conditions, on the germination of P. roebelenii seeds. The fruits were collected from two different locations: Ilha Solteira, western São Paulo State and Jaboticabal in the middle East of the same State. The disseminules (seeds with stucked endocarp) were placed in plastic boxes (gerbox), and the experimental design was entirely randomized in a factorial scheme of 7×2 (seven temperatures conditions: room temperature, constant at 20, 25, 30 and 35°C and alternated at 20-30 and 25-35°C; and two fruit harvesting locations: Ilha Solteira and Jaboticabal, with four replications with 25 seeds each. The disseminules that emitted the germinative intumescence were daily noted until the germinative process got steady, in about 90 days. The germination rate (G%), the germination speed index (GSI), and the means were extracted and compared by the Tukey test. The highest values of germination rate were obtained at 30, 25-35°C and room temperatures. The seeds showed a higher GSI at room temperature. The fruit harvesting locations influenced the germination.